Benzocaine-incorporated smart 1, 3-squaraine dyes: Red emission, excellent stability and cell bioimaging. (February 2020) - Wang, Yigang; Li, Yuanfang; Yan, Qiuming; Liu, Xianglong; Xia, Guomin; Shao, Qingqing; Liang, Kangli; Hong, Liming; Chi, Baozhu; Wang, Hongming
Abstract: The intense and tunable emission of squaraine dyes is highly desirable, but it suffers from nonfluorescent aggregation and intrinsic chemical instability thus restricts its applications. Herein, incorporating benzocaine we synthesized two typical 1, 3-SQs, namely SQ1 and SQ2, both emitted in crystalline states but very weak in solutions. From structural and DFT calculations, this atypical emission behaviors were ascribed to their hydrogen bonding interactions dominated in crystalline states, while the intramolecular motions by the distortion of C–N single bond responded to non/weak emission in solution. Furthermore, the excited state intermolecular dual proton transfer (ESIDPT) was also confirmed for red emissive SQ2 crystals. Importantly, SQ2 exhibited excellent stable against nucleophiles in solutions and biocompatibility, thereby permitted it successfully applied to the cell bioimaging without any encapsulation. This work would be beneficial to improve the practical applications of squaraine dyes in solid state and biology. Graphical abstract: Image 1 Highlights: Benzocaine-incorporated squaraine dyes exhibited crystalline emission but weak in dilute solution. Red emission, excellent stability and biocompatibility permitted SQ2 applied in bioimaging. These smart squaraine dyes, killing two "challenges" with one "structure", would benefit to their practical applications.